1984
DOI: 10.1128/iai.46.3.765-772.1984
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal investigation of bacteriology of human fissure decay: epidemiological studies in molars shortly after eruption

Abstract: In the present investigation, the proportions of Streptococcus mutans, lactobacilli, Streptococcus sanguis, veillonellae, and an unidentified actinomyces-like organism in dental plaque on occlusal fissures of first mandibular molars were monitored at 6-month intervals over a 3-year period in 368 children who were initially in grades 1 or 2. Teeth destined to become decayed exhibited a significant increase in the proportions of S. mutans from 6 to 24 months before the diagnosis of dental decay. Lactobacilli wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
2
4

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 26 publications
5
44
2
4
Order By: Relevance
“…The current study supports the view shared by others (1,2,8,38,42,43,53,63) that caries activity is positively associated with the numbers of mutans streptococci and lactobacilli in saliva and dental plaque. The importance of mutans streptococci in the etiology of human dental decay has been strengthened by the findings that mutans streptococci numbers increase at dental sites destined to become cariogenic, whether they are at fissure sites (11, 39, 43) or at approximal sites (2,8).…”
Section: Correlations Between Variabiessupporting
confidence: 92%
See 1 more Smart Citation
“…The current study supports the view shared by others (1,2,8,38,42,43,53,63) that caries activity is positively associated with the numbers of mutans streptococci and lactobacilli in saliva and dental plaque. The importance of mutans streptococci in the etiology of human dental decay has been strengthened by the findings that mutans streptococci numbers increase at dental sites destined to become cariogenic, whether they are at fissure sites (11, 39, 43) or at approximal sites (2,8).…”
Section: Correlations Between Variabiessupporting
confidence: 92%
“…The importance of Streptoeoeeus mutatis in the initiation of dental decay has been studied extensively (42), Since mutans streptococci and lactobacilli have been itnplicated directly in the initiation and progression of dental caries, these organistns have been associated with caries risk assessment in a number of studies (22,25,37,42,54), The associations of mutans streptococci and lactobacilli to the prevalence of dental caries have been studied extensively throughout the world (I, 3,4,7,13,14,30,31,33,34,53,56,63) but relatively few studies have addressed the problem in North America (8,11,26,32,43,59) and none has addressed the issue of water fluoridation.…”
mentioning
confidence: 99%
“…Among the acidogenic bacteria with a potential to induce dental caries. Streptococcus mutans is considered as the most efficient (16,21) and is generally found in high proportions in the dental plaque of subjects who develop lesions (9,12,17,18). The growth of S. tnutans in dental plaque is promoted by carbohydrates (16) which represent the only source of usable energy for this bacterial species.…”
mentioning
confidence: 99%
“…Veillonellae were generally regarded as commensal bacteria of the oral cavity and the gastrointestinal tract of humans; however, numerous molecular epidemiological studies have found veillonellae to be associated with dental caries (Loesche et al, 1984;Marchant et al, 2001;Becker et al, 2002;Rozkiewicz et al, 2006;Aas et al, 2008;Al-Ahmad et al, 2010;Kanasi et al, 2010;Lima et al, 2010;Ling et al, 2010), as well as the initiation of periodontitis (Kamma et al, 1995;Tanner et al, 1996;Socransky et al, 1998), both of which are polymicrobial diseases of the oral cavity. Some species of Veillonella can also cause monomicrobial infections of the joint (Marchandin et al, 2001) or life-threatening bacteremia in immunocompromised patients (Strach et al, 2006).…”
Section: Introductionmentioning
confidence: 99%